Treated domestic sewage: kinetics of Escherichia coli and total coliform inactivation by oxidation with hydrogen peroxide - Gean Delise L. P. Vargas (Química Nova, 2013)
Hydrogen peroxide has been used for decades in developed countries as an oxidizing agent in the treatment of water, domestic sewage and industrial effluents. This study evaluated the influence of the concentration of H2O2 and pH on the inactivation of Escherichia coli cells and the disinfection of sewage treated. The results showed that the inactivation rate increased with pH and H2O2. The presence of other contaminants dissolved in the effluent is probably the cause of these differences, because E. coli inactivation in synthetic wastewater was found to be much faster than in the real treated domestic sewage.